Delayed diagnosis of nasopharyngeal carcinoma in a patient with early signs of unilateral ear disorder (Faculty of Medicine Universitas Indonesia, 2014)
Nasopharyngeal carcinoma (NPC) is the most frequent head and neck malignancy in Indonesia. Misdiagnosis of NPC is common because of unspecific symptoms as unilateral ear complaint. This case reminds doctors of the early symptoms of NPC and of other factors which lead to misdiagnosis and addresses also patients and their families. Reported is a 44 years old man with unilateral ear disorder that had been treated by otorhinolaryngologists, an ophthalmologist, a neurologist, and dentist first, but diagnosed with nasopharyngeal carcinoma stage IVA (T4N1M0) one year later. NPC has unspecific early symptoms such as unilateral ear disorder. Primarily doctors, but also patients and their families should be aware of unilateral ear complaint.Keywords: misdiagnosis, nasopharyngeal carcinoma, unilateral ear disorders